Effect of the Relative Clause in the Prophet’s Saying “The House Which” on Social Security - Rababa’h, Mohammad Mjalli Ahmad (Dirasat: Shari'a and Law Sciences, 2023)
Objectives: The aim of this research is to collect the hadiths in which “the house which” is mentioned, and to analyze the relative clauses in them in order to reveal the impact of these meanings on the safety and welfare of the society. Methods: This research follows the complete inductive approach for the hadith, generally showing its degree of acceptance. The analytical and deductive approach was adopted as well to present the semantic indications of the relative clauses and the positive impact on society. Results: The total number of hadiths in which “the house which” is mentioned fifteen times; eight of them have no indication of societal peace, however, the other seven have. The most influential of them are: in which Allah is remembered, or the Qur'an is read. Then the house in which a Muslim is keen to establish the rituals of religion. On the other hand, the most dangerous house is the one in which there is a portrayal, followed by the house in which the effeminate enters. Conclusions: The research recommends that practical studies should be conducted with regard to the impact of the schools of the Qur’an on the local community, as well as studies on other types of houses such as homes of people with disabilities, or those near nightclubs, exhibitions, and fashion houses; To find out more about its societal impact.